A new squash specific incremental field test - Micklewright, D.; Papapdopoulou, E. (International Journal of Sports Medicine, 2008)
The purpose of this study was to develop a practical and reliable squash specific incremental test for estimating maximal oxygen uptake (V?O2max). V?O2max was measured using breath-by-breath online gas analysis among 11 male and 10 female squash players during a maximal incremental running treadmill protocol. All subjects performed a specially designed maximal squash specific incremental test (SSIT) until fatigue on two separate occasions. There were positive intra-class correlations for the two SSIT trials for time to fatigue (r = 0.998, p < 0.001) but the second trial was shorter (t = 2.7, p < 0.05) due to less stable scores among female players. A positive correlation was found between SSIT performance and V?O2max (r = 0.924, p < 0.001). SSIT time to fatigue and V?O2max regression equations were used to produce a table to predict V?O2max from SSIT performance. SSIT was found to be a reliable and valid method of estimating V?O2max among squash players. A balance between usability and squash specificity was achieved in the design of the SSIT without jeopardising its purpose of estimating V?O2max. SSIT is inexpensive, quick to set up and simple to administer compared to other squash specific tests and can be used with novice through to elite players.